Status of Water Quota for Residential Building Construction and Compilation of National Standards - BAI Le; LI Enkuan; FU Xinfeng; JIA Yifei (Renmin Zhujiang)
Considering that there is no national standard for water quota in constructing residential buildings,this paper summarizes the existing problems in water quota compilation for residential building construction in 31 provinces of China and teases out related concepts and their connotations in this regard.On this basis,the construction area and water consumption of residential buildings during the construction period are investigated,and scientific and reasonable water use boundary and measurement benchmarks are established.Given the published provincial water quota,a clustering analysis method is used to partition and classify the water consumption quota,and the water quota is calculated by empirical and statistical methods.Combined with the requirements of the current water-saving policy and the actual water use,the water quota value is finally determined.The results show that the standard rate of the provincial water quota is12.5%~40.0%.This quota takes into account the actual water use and water-saving potential of residential building construction at this stage and can measure the water-saving level in the future period.The water quota is reasonable,scientific,and advanced,which can be used in the application and approval of temporary water use for residential building construction,as well as water-saving management such as the management of planned water use.In this way,the standard system of the water quota in China is further improved.